A música coral cristã e seus conceitos históricos a partir da obra Os Céus Proclamam do Maestro Rev. João Wilson Faustini - Reis, Natalia Macedo Guimarães dos (2021)
This study aims to point out the techincal and historical-cultural contributions of the work carried out by the Maestro Rev. João Wilson Faustini, by means of choral music, especially in evangelical churches with a reformed tradition, based on his work “The Heavens Proclaim”. In addition to the religious and liturgical objective, the conductor has intended by means of this collection, to disseminate and facilitate access to a repertoire, which in our culture, is not as well known and / or appreciated - the erudite (classical) music. In Brazil, this kind of music is not part of mass communication and media programs, which limits the access of a large part of the population to these works, of various styles and periods of history. “The Heavens Proclaim” work has contributed for a first contact from a large number of people to the songs of great classical composers from the world music scope. It cooperates with individual evolution, expanding their knowledge and feelings, besides providing a historical, social and cultural enrichment, both individuallly and as for the community where they have been placed